Characterization by sex of patients with acute coronary syndrome with ST segment elevation, subjected to coronary intervention. - Nadia Sanchez Torres; Jesús M. Pérez del Todo; Ernesto del Pino Sanchez; Geovedy Martínez García; Grisel Guevara Mirabal; Alexei Suarez Rivero (ECIMED, 2011)
Introduction: The ischemic heart disease is the first cause of death in our country. Differences exist among sexes as for the answer to the different risk factors, the presentation forms and the answer to the treatment. The aim of this study is determinate the differences between men and women with Acute coronary syndrome with ST segment elevation subject to percutaneous coronary intervention at the Cardiology and cardiovascular surgery Institute.Method: It was carried out a retrospective, descriptive, traverse study, of 659 patients, subjected to percutaneous coronary intervention at the Cardiology and Cardiovascular Surgery Institute with diagnosis of acute coronary syndrome with ST segment elevation in the period understood between January of the 2003 and January of the 2009.Results: The masculine sex 75, 6%, prevailed. The mean age of the women was 62, 21 ± 12, 27 vs 59, 13 ± 11,16 years that of the men. It was a significant prevalence of the risk factors in males, with the only exception of the dyslipidaemia that had a similar behaviour in both sexes (p <0, 05). The illness of 1 vessel was superior in men (72, 8% p=0, 0008), being the left anterior descending artery the affected 49, 1%, in both sexes (p = 0, 08). The elective PCI represented 68%. The rate of success of the PCI went superior to 90% behaving in a similar way in both genders.Conclusions: Differences exist with regard to the age and main coronary risk factors, a different trend was observed in relation to the number of sick vessels and to the result of the interventional proceeding.